Leaves aqueous extract as a cytological stain for buccal cell screening / Mohd Nazri Abu ... [et al.] - Abu, Mohd Nazri; Zaimy, Nurizan; Sahlan, Suwadi Aryadiy; Zulkifle, Nur Atikah; Mohd Azlan, Siti Sarra Hazwani (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
This study describes the preparation and use of Alternanthera dentata (purple knight), Alternanthera ficoidea (grenadine), Brassica oleracea (red cabbage), Amaranthus dubius (red spinach) and Lawsonia inermis (henna) for the differential staining of buccal cells to find out its staining effect on nuclear and cytoplasm as an alternative to Papanicolaou stain in cytology laboratory. The leaves aqueous extracts were tested with or without addition of Aluminium chloride (AlCl3) mordant using regressive Papanicolaou staining procedure as a standard with minor modification. All the leaves extract was measured for pH, physical colour concentration, qualitative and quantitative staining intensity and ability. Statistical data were calculated by using Weighted-Kappa analysis showed a fair correlation between staining intensity of leaves aqueous extract dye with Papanicolaou stain while, One-way ANOVA showed no significant difference between leaves aqueous extract and Papanicolaou stain. Therefore, the leaves aqueous extracts stain were not comparable to the standard. As a conclusion, the leaves aqueous extract used in this study has the ability to stain both nucleus and cytoplasm by its own colour; however, the colour intensity is incomparable with Papanicolaou stain as the standard.